Socioeconomic changes in Tondo foreshore an evaluation of a slum upgrading project - Munarriz, Mayu T. (The Philippine Review of Business and Economics, 1988)
This paper examines socioeconomic changes brought about by the Tondo Foreshore Development Project to residents' living conditions after project implementation. It compares levels of income, school enrollment and pursuance of high school education, perceived community problems and health conditions before and after project implementation. Significant differences in these variables were found, suggesting that an examination of project feasibility in the light of its socioeconomic impacts permits a realistic and comprehensive method of project evaluation. Thus, socioeconomic impact studies of this type are recommended.